Examining Aggression, Rumination and Self-Control under the Influence of Emotion Regulation Training and Mindfulness Training in Students with Low Academic Performance - Mehraban, Rogaiye; Hosseini Nasab, Seyyed Davood; Alivandi Vafa, Marziye (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Academic performance has the main role in the students' future success. The purpose of this study was to examine aggression, rumination and self-control under the influence if effectiveness of emotion regulation training and mindfulness training in female students with low academic performance in Junior high school in Tabriz. Methods: The research design was semi-experimental with pre-, and post-test, two experimental groups and one control group. The statistical population included all the female junior high school students in Tabriz, region one with low academic performance among them 75 students were selected as the research sample and randomly assigned in three groups (two experimental and one control group). The instruments of data collection included: Tangey's self-control scale, Boss & Perry' aggression questionnaire and Nolen-Hoeksema & Marrrow' mental rumination scale. Emotion regulation package was performed in one experimental group and mindfulness package was performed in the other experimental group. Control group received no intervention. The research hypotheses were analyzed by one way ANCOVA.  Results:  The findings indicated that the method of emotion regulation training is more effective on aggression than mindfulness training, but regarding rumination and self-control, no significant difference was observed between two groups. Also, the results showed that there was significant difference among two experimental groups, i.e. emotion regulation training and mindfulness training and control group regarding aggression, rumination and self-control and effectiveness of these methods on decreasing mental rumination and aggression and increasing self-control was confirmed. (P=0.05). Conclusion: The results of this research showed that the use of emotion regulation and mindfulness methods can be effective in reducing aggression and mental rumination and increasing self control of students with low academic performance